Creation of the Kingdom of Poland in the Discourse of the Russian Press - M. S. Belousov; A. S. Belousov; A. I. Kuru (Научный диалог, 2021)
This article is devoted to the analysis of the rhetoric presented in the Russian press in 1814—1818 regarding the imperial policy in the newly annexed Kingdom of Poland. The aim of the authors is to show that it is necessary to separate the real policy of the Russian autocracy in this territory from the images created first by French publicists, and then repeatedly exaggerated by Russian journalists. It is noted that Alexander I in 1814—1818 appears on the pages of French publications as a tsar-liberator. It is shown that these stories were quickly picked up by Russian newspapers and magazines and, as a result, a paradoxical picture emerged: for several years the mass media convinced the Russian society that the Russian Tsar was the new Polish national sovereign. It is argued that this, of course, caused rejection in conservative circles and among advanced Westerners such as Vyazemsky or Turgenev. It is concluded that it is the dominant discourse that can be considered, on the one hand, one of the factors in the emergence of the Decembrist movement, and on the other, a “trap” for Alexander I, since the liberal rhetoric of the press over time began to diverge more and more from the real policy of the Russian autocracy.